Uncertainty and the subject-to qualification: the auditor's responsibility - Konrath, Larry F (Journal of accountancy, 1985)
In earlier years, auditors attempted to combat misleading financial reporting by using a ''subject-to'' phrase in their qualified financial statements. The phrase was intended to cover both uncertainty and lack of fairness in the presentation. Now, it has come to mean uncertainty about how future events might affect conclusions drawn from the statements. Arguments supporting and opposing this qualification focus on whether or not the auditor should be expected to predict uncertainties. Audits of troubled companies raise the issue of whether the ''going concern'' basis of accounting is appropriate in that situation. A compromise between remaining silent or using the ''subject-to'' qualification would be the inclusion of a middle paragraph that directs attention to pervasive uncertainty. The ''subject-to'' qualification, as well as disclaimers and middle paragraphs, should be eliminated as suggested by the 1982 Accounting Standards Board exposure draft and the Canadian Institute of Chartered Accountants.